2012
DOI: 10.4103/0971-6203.94742
|View full text |Cite
|
Sign up to set email alerts
|

Impact of edema and seed movement on the dosimetry of prostate seed implants

Abstract: This article summarizes current knowledge concerning the characterization of prostatic edema and intra-prostatic seed movement as these relate to dosimetry of permanent prostate implants, and reports the initial application to clinical data of a new edema model used in calculating pre- and post-implant dose distributions. Published edema magnitude and half-life parameters span a broad range depending on implant technique and measurement uncertainty, hence clinically applicable values should be determined local… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…Our appreciation that a clinically significant extent of seed migration was occurring with this new product stems from our previous experience in studying seed migration [ 9 ]. Although this previous experience was from a different institution, the products and techniques were similar to our current methods and included one common physician.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our appreciation that a clinically significant extent of seed migration was occurring with this new product stems from our previous experience in studying seed migration [ 9 ]. Although this previous experience was from a different institution, the products and techniques were similar to our current methods and included one common physician.…”
Section: Discussionmentioning
confidence: 99%
“…While using this new product, routine quality assurance revealed qualitatively significant migration of strands in six of the 26 patients, often to bizarre locations, such as the ischiorectal fossa. This migration was particularly unusual for our institution, as we have previous experience in patients with serial imaging and no such significant migration [9]. We initiated an additional Day 30 CT scan in these patients to analyze seed fixity.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…To determine the quality of the implantation, we perform a CT scan immediately following the implantation and use it to generate a second treatment plan, called the Day 0 treatment plan. After the prostate edema has resolved in approximately a month, another CT scan is performed to generate the Day 30 treatment plan (16‐19) …”
Section: Methodsmentioning
confidence: 99%
“…Several studies have investigated the influence of edema on post-implant dosimetry (Chira et al 2013, Tejwani et al 2012, Waterman et al 1998, Sloboda et al 2012, Yue et al 2006, Sloboda et al 2010, Chen et al 2000and Dogan et al 2002. Chira et al (2013) have shown that a prostate volume increase of 10% during brachytherapy can lead to an increase in D90 (dose coverage of 90% of the prostate volume) at Day30 of approximately 11.7% in comparison to the D90 measured at Day1.…”
Section: Introductionmentioning
confidence: 99%